The development of a harmonised business model for South Africa and the SADC sub-region - Sodeinde, Taiwo Oluseyi (Department of Commercial Law, 2015)
Business rescue regime has led to dramatic improvement in ailing organizations across the globe in recent years. This work critically examines current South African business rescue option in the context of her role in the SADC sub-region. A robust model, taking into consideration, the legal, socio-cultural, political and economic diversity of SADC members is proposed. It is believed that the model can serve as a template for other regions in the continent.